The role of care partners in medical visits of older adults with hearing loss and dementia: A national study. Issue 3 (30th November 2022) - Powell, Danielle S.; Reed, Nicholas S.; Oh, Esther; Samus, Quincy M.; Deal, Jennifer A.; Wolff, Jennifer L.
Abstract: Background: Dementia and hearing loss (HL) are conditions, which restrict communication ability and amplify the difficulty of implementing effective care coordination and communication with medical providers. We examined how the presence of HL and dementia influence communication with medical providers, and the role of involved care partners during medical visits. Methods: Drawing on responses from 7070 community‐dwelling older adults who participated in the 2015 National Health and Aging Trends Study, we used logistic regression to quantify care partner accompaniment to medical visits and the role care partners assume during visits by older adult hearing and dementia status. Results: Nearly 4 in 10 older adults with dementia also reported HL. Eighty‐two percent of older adults with both HL and dementia were accompanied to medical visits by a care partner. Those with HL and dementia were six times more likely to be accompanied by a care partner to medical visits than those with neither condition (OR: 6.04; 95% CI:4.06, 8.99). Care partners of older adults with both (vs neither) HL and dementia were more actively engaged in: (1) facilitating understanding between the older adult and doctor (OR: 4.55, 95% CI:2.68, 7.71); (2) asking or telling the doctor information (OR: 6.13, 95% CI:3.44, 10.9); and (3) reminding the older adult of their questions (OR: 2.52, 95% CI: 1.66, 3.83). Conclusions: Care partners have an active role during medical visits of older adults with HL and dementia. Efforts to support care partner engagement and teach advocacy skills may close gaps in care quality for the subgroup of older adults who are living with HL and dementia.